VAN VELSEN, Ilse e Femke. Fighting the Silence: Sexual Violence against Women in Congo e Weapon of War: confessions of rape in Congo. Amsterdã, Ifproductions, 2008/09. - Rovai, Marta Gouveia de Oliveira (Outros Tempos: Pesquisa em Foco - História, 2010)
Boa Leitura!